THE TEACHERS’ UNDERSTANDING OF CONTENT AND PROCESS STANDARDS OF 2013 CURRICULUM AND THEIR ABILITIES IN PREPARING ENGLISH LESSON PLAN - Rusydi Rusydi; Usman Kasim; Iskandar Abdul Samad (Universitas Syiah Kuala, 2020)
Teachers’ understanding of how both content and process standards affect their preparation on the lesson plan (RPP) is still weak. There is a lack of learning assessment, basic competence, indicators, teaching materials, and learning models and their use which is not appropriate based on the Indonesian 2013 curriculum. This research was aimed at finding out the English teachers’ understanding of two main elements of the 2013 curriculum; content and process standards that lead the teachers to prepare appropriate lesson plan (RPP) which has a direct interaction with the instructional process. The selected samples were six English teachers from different levels of junior high schools in Banda Aceh. The questionnaire and interview guide were used as research instruments. The result of the teachers’ understanding of the content standard of 2013 curriculum showed that the English teachers had an fairly good understanding of the standard of the content of the curriculum 2013 as indicated by an average score of 65.23, while teachers’ understanding of process standard of curriculum 2013 showed the English teachers already had a good understanding of the standard of the content of the 2013 curriculum, as shown by an average score of 72.21. Overall, the average score of lesson plan (RPP) preparation was 65.16 which was categorized as being fairly good.